Staged equity financing - Magnus Blomkvist; Timo P. Korkeamaki; Tuomas Takalo (Bank of Finland, 2020)
We propose a rationale for why firms often return to the equity market shortly after their initial public offering (IPO). We argue that hard to value firms conduct smaller IPOs, and that they return to the equity market conditional on positive valuation signal from the stock market. Thus, information asymmetry is not a necessary condition for staged financing. We find strong support for these arguments in a sample of 2,143 U.S. IPOs between 1981-2014. Hard to value firms conduct smaller IPOs, and upon positive post-IPO returns, they tend to return to the equity market quickly, following the IPO.
URN:NBN:fi:bof-202008252284
Keywords: G14; G24; G32; 330; IPOs; security issuance; sequential financing